1969
DOI: 10.1203/00006450-196907000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Convulsive Disorders in Young Children: I. Incidence of Febrile and Nonfebrile Convulsions by Age and Other Factors

Abstract: I n a cohort of 18,500 newborn infants, those who had experienced one or more convulsions were studied. Data were available for the unaffected as well as for the affected children. All families were members of a prepaid medical care program that provides comprehensive medical care.By five years of age, two percent of the 18,500 children had had one or more febrile convulsions; one percent had had nonfebrile convulsions. The incidence of the first nonfebrile seizure was highest during the first month of life; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
81
3
3

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(99 citation statements)
references
References 2 publications
12
81
3
3
Order By: Relevance
“…Based on literature review, the incidence of febrile seizures in the second year of life is reported to be 1 to 2 per 1000 children per month in the general population (estimated prior to the introduction of many of the vaccines in the current pediatric schedule). [23][24][25][26][27][28][29] In addition, the number of febrile seizures observed in the MMRV AMP group is consistent with what would be expected for children in this age range based on estimates from incidence rates and times of follow-up. The observed imbalance between groups in the numbers of first occurrences of febrile seizures outside the primary safety period is not likely to be related to any true incidence difference between the groups.…”
Section: Discussionsupporting
confidence: 60%
“…Based on literature review, the incidence of febrile seizures in the second year of life is reported to be 1 to 2 per 1000 children per month in the general population (estimated prior to the introduction of many of the vaccines in the current pediatric schedule). [23][24][25][26][27][28][29] In addition, the number of febrile seizures observed in the MMRV AMP group is consistent with what would be expected for children in this age range based on estimates from incidence rates and times of follow-up. The observed imbalance between groups in the numbers of first occurrences of febrile seizures outside the primary safety period is not likely to be related to any true incidence difference between the groups.…”
Section: Discussionsupporting
confidence: 60%
“…We undertook a study to determine the frequency of MRI-detected brain abnormalities andFebrile seizures (FS) are common, affecting 2-5% of children by 6 years of age (van den Berg & Yerushalmy, 1969;Verity et al, 1985) and are associated with an increased risk of subsequent epilepsy. Epilepsy develops in 2-4% of children with a history of FS, four times more fre- (Nelson & Ellenberg, 1978;Annegers et al, 1979;Verity et al, 1985).…”
mentioning
confidence: 99%
“…While a specific association of childhood febrile seizures with temporal lobe epilepsy remains to be established, there is little doubt that early febrile seizures are associated with an excess risk of subsequent recurrent afebrile seizures generally (Van den Berg & Yerushalmy, 1969;Hauser & Kurland, 1975;Nelson & Ellenberg, 1976). The aetiological question is whether febrile seizures 'kindle' later seizures, whether they indicate an epileptic predisposition, or whether both processes are involved.…”
mentioning
confidence: 99%
“…The rate for the remainder of the first year stabilized at a monthly rate of about 0-20 per 1000 and continued to decline unevenly thereafter. By the age of 5, about 10 per 1000 of the cohort had had at least one afebrile fit (Van den Berg & Yerushalmy, 1969).…”
mentioning
confidence: 99%